Effect of Organizational Citizenship Behavior on Employee Performance at PT Surya Dermato Medica Palembang - Fatma Triani; Hamid Halin; Muhammad Wadud (International Journal of Community Service & Engagement, 2020)
This study aims to investigate the effect of organizational citizenship behavior on employee performance at PT Surya Dermato Medica Palembang. The total sample of 51 was all employees of PT Surya Dermato Medica. Data were collected through observation and questionnaires, and analyzed using simple linear regression on SPSS V23. The results show that organizational citizenship behavior has a positive and significant effect on employee performance. The R2 value of 0.538 indicates that employee performance can be explained by organizational citizenship behavior by 53.8%.